1991
DOI: 10.1083/jcb.113.4.919
|View full text |Cite
|
Sign up to set email alerts
|

Integrins alpha v beta 3 and alpha v beta 5 contribute to cell attachment to vitronectin but differentially distribute on the cell surface.

Abstract: Abstract. We investigated the role of the integrins c~vB3 and c~v/~5 in mediating vitronectin adhesion of three phenotypically distinct cell types. M21 human melanoma cells and H2981 lung carcinoma cells use both otv-containing integrins in adhering to vitronectin while UCLA-P3 lung carcinoma cells adhere exclusively with otv/~5. Specifically, monoclonal antibodies directed to functional epitopes on both receptors were required to block adhesion of M21 or H2981 cells while adhesion of UCLA-P3 cells to vitronec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
182
1
4

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(197 citation statements)
references
References 44 publications
10
182
1
4
Order By: Relevance
“…Indeed, inclusion of the function-blocking anti-␣ v ␤ 5 integrin antibody P1F6 in adhesion experiments completely inhibited CHO-B2 adhesion to vitronectin and partially blocked adhesion to Ang-2 (data not shown). Initial studies of ␣ v ␤ 5 -mediated cell adhesion to vitronectin established that ␣ v ␤ 5 does not localize to focal contacts or associate with the actin cytoskeleton (34). Subsequent studies found that activation of protein kinase C indirectly via epidermal growth factor stimulation or directly with phorbol esters promoted ␣ v ␤ 5 -mediated cell spreading, focal contact formation, and migration on vitronectin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inclusion of the function-blocking anti-␣ v ␤ 5 integrin antibody P1F6 in adhesion experiments completely inhibited CHO-B2 adhesion to vitronectin and partially blocked adhesion to Ang-2 (data not shown). Initial studies of ␣ v ␤ 5 -mediated cell adhesion to vitronectin established that ␣ v ␤ 5 does not localize to focal contacts or associate with the actin cytoskeleton (34). Subsequent studies found that activation of protein kinase C indirectly via epidermal growth factor stimulation or directly with phorbol esters promoted ␣ v ␤ 5 -mediated cell spreading, focal contact formation, and migration on vitronectin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Another suggestion is that they are a normal adhesion structure found in highly motile cells (Nermut et al, 199 1). The results of studies on carcinoma cell adhesion and spreading have suggested that integrins in point contacts are unable to interact with the cytoskeleton (Wayner et al, 1991). Recent antibody blocking experiments performed with astrocytes that express both point contacts and focal contacts demonstrate that point contacts can be functional sites of adhesion (Tawil et al, 1993).…”
Section: Point Contactsmentioning
confidence: 99%
“…For example, the fibronectin receptor, «5ß,, concentrates in focal contacts in cells spread on a substrate of fibronectin ; the vitronectin receptor, aß3, is in focal contacts in cells spread on vitronectin ; and on a collagen substrate, the collagen receptor, a2ß,, is in focal contacts (Singer et al, 1988;Dejana et al ., 1988;Fath et al ., 1989;Carter et al, 1990). However, it is puzzling that the vitronectin receptor, «vß5 , does not localize to focal contacts (Wayner et al, 1991), even though it contains sequence motifs previously demonstrated to be important in receptor localization to these adhesion sites (McLean et al ., 1990;Ramaswamy and Hemler, 1990;Marcantonio et al, 1990) . Thus, the molecular mechanisms ofthe regulation ofintegrin receptor distribution and the specific contributions of the various aspects of receptor function to this process are still unknown .…”
mentioning
confidence: 99%